Perancangan Tahap Pra-Produksi Dalam Produksi Video Stop Motion: Desain Komunikasi Visual - Aisyah Zahwah Andrasari; Widyasari Widyasari; Bayu Setiawan (Pusat Riset dan Inovasi Nasional, 2026)
Stop motion technique is a combination of photos taken sequentially to create the illusion of movement. Stop motion video is also able to increase visual appeal and also strengthen the delivery of the message contained to the audience. This study aims to design and produce audio-visual works based on stop motion animation techniques with a pixilation approach that raises the theme of